How to manage KRAS G12C-mutated advanced non-small-cell lung cancer - Biagio Ricciuti; Alessia Mira; Elisa Andrini; Pietro Scaparone; Sandra Vietti Michelina; Federica Pecci; Luca Cantini; Andrea De Giglio; Giuseppe Lamberti; Chiara Ambrogio; Giulio Metro (BioExcel Publishing Ltd, 2022)
Constitutive KRAS signalling drives tumorigenesis across several cancer types. In non-small-cell lung cancer (NSCLC) activating KRAS mutations occur in ~30% of cases, and the glycine to cysteine substitution at codon 12 (G12C) is the most common KRAS alteration. Although KRAS mutations have been considered undruggable for over 40 years, the recent discovery of allelic-specific KRAS inhibitors has paved the way to personalized cancer medicine for patients with tumours harbouring these mutations. Here, we review the current treatment landscape for patients with advanced NSCLCs harbouring a KRAS G12C mutation, including PD-(L) 1-based therapies and direct KRAS inhibitors as well as sequential treatment options. We also explore the possible mechanisms of resistance to KRAS inhibition and strategies to overcome resistance in patients with KRAS G12C-mutant NSCLC.